Strategic Agility: A prospect for sustainable performance of micro-businesses in South-Eastern Nigeria - Monyei, Ezieshi Francis; Okeke, Patrick Anene; Nwosu, Kanayo Chike (Goodwood Publishing, 2021)
Purpose: To investigate the role strategic agility plays in the sustainable performance of micro-businesses, while specifically, it sort to examine the link between micro-businesses decision-making and technology adoption in South-eastern Nigeria Research methodology: A survey research method was adopted with a population quoted at 210 Micro-business registered owners in South-eastern Nigeria. The sample size of 136 was arrived at using Krejcie and Morgan's (1970) formula. A questionnaire set was designed for data collection and analyzed using the Linear Regression Statistics at a 5% level of significance. Results: Decision-making and technology adoption have a statistical significant relationship with Micro-businesses in South-eastern Nigeria (R2 = .959; F = 1180.390; p-value < 0.05). Limitations: The study did not cover all the five states in the region where the study was conducted. Contribution: The study excruciates strategic agility's role, its prospect for Micro-businesses, and its link with sustainable performance in a turbulent and dynamic business environment.